Figure 5 from: Eberhardt U, Beker HJ, Borgen T, Knudsen H, Schütz N, Elborne SA (2021) A survey of Hebeloma (Hymenogastraceae) in Greenland. MycoKeys 79: 17-118. https://doi.org/10.3897/mycokeys.79.63363 - Eberhardt, Ursula; Beker, Henry J.; Borgen, Torbjørn; Knudsen, Henning; Schütz, Nicole; Elborne, Steen A. (Zenodo, 2021)
Figure 5 A Pruned quasi-median network of the Hebeloma alpinum complex, H. arcticum and H. louiseae. Circles shared by two or more taxa or collections from two regions, from Greenland (G) or collected elsewhere, are divided according to the number of representatives for each class B ML result for Hebeloma subsect. Crustuliniforme, based on concatenated ITS, RPB2 and Tef1a data, rooted with H. louiseae. Thick branches indicate bootstrap support of at least 80% (450 bootstrap replicates). Species are represented by three collections (if available); Hebeloma arcticum by four collections including the holotype.